Redescription of immature stages of central European fireflies, Part 2: Lamprohiza splendidula (Linnaeus, 1767) larva, pupa and notes on its life cycle and behaviour (Coleoptera: Lampyridae) - Novák, Martin (Zootaxa, 2018)
The mature larva of the firefly Lamprohiza splendidula (Linnaeus, 1767) is thoroughly redescribed and illustrated with detailed images, including scanning electron microscope figures. External sense organs, structure of tergal plates and their significance are discussed, as well as photic manifestation of the larvae and pupae and prey hunting in larvae. Male and female pupae are briefly described, with notes on their developmental changes and behaviour, and the life cycle outlined.